Event-related potential changes due to early-onset Parkinson's disease in parkin (PARK2) gene mutation carriers and non-carriers. Issue 7 (July 2020) - Uslu, Atilla; Ergen, Mehmet; Demirci, Hasan; Lohmann, Ebba; Hanagasi, Hasmet; Demiralp, Tamer
Highlights: Oddball target P3 and CPT NoGo P3 are reduced and delayed in patients with EOPD. EOPD patients showed less negative N1 and increased P2 waves. There was no difference between ERPs of PARK2 mutation carriers and non-carriers. Abstract: Objective: To investigate cognitive functions in non-demented patients with early-onset Parkinson's disease (PD), and to compare PARK2 gene mutation carriers and non-carriers by means of event-related brain potentials (ERPs). Methods: The participants comprised patients with early-onset PD (EOPD) and healthy controls (HC). Patients with EOPD were divided into two groups as carriers of known pathogenic variants of PARK2 gene (EOPD-PC) and non-carriers of genes involved in familial PD (EOPD-NC). ERP data were collected during auditory oddball and visual continuous performance test (CPT). Results: Both EOPD groups (EOPD-PC and EOPD-NC) displayed reduced and delayed P3 in response to oddball target and CPT NoGo. CPT Go P3 was reduced in EOPD-NC but not in EOPD-PC. Oddball target N1 was reduced and P2 was enhanced in both EOPD-PC and EOPD-NC. In both cognitive tasks, RTs were prolonged and accuracy was lower in EOPD-PC and EOPD-NC. Conclusions: We found several EOPD-related neurophysiologic changes, implying impairments in cognitive functions. Pairwise comparisons between EOPD-PC and EOPD-NC revealed no significant ERP marker. Significance: In this study, the confounding effect of normative aging was somewhat excluded compared with many previous studies. In contrast with the many oddball studies in non-demented PD, we clearly observed reduced and prolonged P3 in early-onset PD. Our NoGo P3 findings also contribute to the limited ERP research concerning response inhibition.